Novel MoSi2 catalysts featuring surface activation as highly efficient cathode materials for long-life Li–O2 batteries. Issue 1 (4th December 2019) - Dang, Congcong; Wang, Yu; He, Biao; Zhang, Weibin; Dang, Feng; Wang, Hongchao; Du, Yong
Abstract : The surface conditions of MoSi2 particles and the stable crystal structure contribute to the great electrochemical performance of Li–O2 batteries. Abstract : Searching for highly efficient and low cost electrocatalysts is an urgent challenge to provide high capacity and long cycle life Li–O2 batteries (LOBs). In this work, the highly efficient electrocatalytic properties of MoSi2 were first demonstrated using particles prepared by a solid–state reaction method. The surface was activated, playing a dominant role in the electrocatalytic performance. After acid etching to remove SiO2 impurities arising from the surface oxidation, MoSi2 exhibited excellent bifunctional electrocatalytic properties for LOBs. Mo 6+ on the surface contributed to the initial low overpotentials of 0.45 V (3.2 V for the OER and 2.75 V for the ORR) and transformed into Mo 4+ for a long cycle life. As a consequence, outstanding rate capabilities of 12 708 mA h g −1 at 100 mA g −1 and 10 794 mA h g −1 at 800 mA g −1, and excellent cycle durability of 215 and 90 cycles at a limited capacity of 1000 mA h g −1 at 200 and 500 mA g −1, respectively, were obtained for the MoSi2 cathode.